2018
DOI: 10.33772/jitro.v5i3.4885
|View full text |Cite
|
Sign up to set email alerts
|

Penampilan Produksi Sapi Aceh Umur Satu Hari, Umur Sapih, dan Umur Satu Tahun

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui penampilan produksi sapi aceh di BPTU-HPT Indrapuri Aceh. Materi penelitian yaitu sapi aceh umur satu hari, umur sapih, dan umur satu tahun sebanyak 159 ekor. Metode penelitian adalah studi kasus berdasarkan data bobot lahir, bobot sapih, bobot satu tahun beserta ukuran tubuhnya. Data dianalisis menunjukkan bahwa sapi jantan memiliki bobot lahir 13,66±1,08 kg, bobot umur 205 hari 71,60±7,92 kg dan bobot  umur 365 hari 104,66±11,72 kg.  Sapi betina memiliki bobot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
3
1
1
Order By: Relevance
“…The results of this study were higher than those reported by Wijono et al [6] stated that the mean BW, WW (205 days) and YW (365 days) of OG cattle were 22.34 ± 2.96 kg, 84.14 ± 17.76, and 120.97 ± 27.45 kg, respectively. The results of this study were also higher than the results reported by Ikhsanuddin et al [9] that in Aceh cattle BW was 13.66 ± 1.08 kg, WW was 71.60 ± 7.92 kg (205 days old), and YW was 104.66 ± 11.72 kg (365 days old). However, the WW and YW of OG cattle of this study were not much different from the results of research of Prihandini et al [10] who reported that WW and YW of OG cattle were 109.10 ± 18.35 kg and 132.70 ± 19.93 kg, respectively, and from the result of research of Sumadi et al [11,12] who reported that WW of Ongole Grade cattle in Kebumen was 119.40 ± 36.61 kg.…”
Section: Resultscontrasting
confidence: 80%
“…The results of this study were higher than those reported by Wijono et al [6] stated that the mean BW, WW (205 days) and YW (365 days) of OG cattle were 22.34 ± 2.96 kg, 84.14 ± 17.76, and 120.97 ± 27.45 kg, respectively. The results of this study were also higher than the results reported by Ikhsanuddin et al [9] that in Aceh cattle BW was 13.66 ± 1.08 kg, WW was 71.60 ± 7.92 kg (205 days old), and YW was 104.66 ± 11.72 kg (365 days old). However, the WW and YW of OG cattle of this study were not much different from the results of research of Prihandini et al [10] who reported that WW and YW of OG cattle were 109.10 ± 18.35 kg and 132.70 ± 19.93 kg, respectively, and from the result of research of Sumadi et al [11,12] who reported that WW of Ongole Grade cattle in Kebumen was 119.40 ± 36.61 kg.…”
Section: Resultscontrasting
confidence: 80%
“…Sapi aceh merupakan kekayaan sumberdaya genetik yang saat ini mulai mengalami ancaman baik dari aspek jumlah maupun kemurniannya. Hal ini disebabkan masuknya breed sapi luar yang tidak terkontrol (Ikhsanuddin et al, 2018).…”
Section: Pendahuluanunclassified
“…Aceh cattle production performance includes body weight and body size as well as Daily Weight Gain (PBBH) pre sapih and post sapih. According to Ikhsanuddin et al, (2018) (Gunawan and Jakaria, 2011).…”
Section: Aceh Cattle Production Performancementioning
confidence: 99%
“…High market demand and the insistence on living needs lead to high levels of livestock production from the population, especially high-productivity livestock, so that the remaining livestock have a low productivity performance on average (Ikhsanuddin et al, 2018). If this condition is not resolved in the next few generations, it is feared that there will be a decrease in livestock productivity (Ikhsanuddin et al, 2018). Solving this problem should involve various parties, such as the Livestock Service, universities, research institutes, local governments, associations, traders, and breeders.…”
Section: Restrictions On Livestock Expenditurementioning
confidence: 99%